Recent Advances In Harmony Search Algorithm - Geem, Zong Woo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Nowadays, music-inspired phenomenon-mimicking harmony search algorithm is fast growing with many applications. One of key success factors of the algorithm is the employment of a novel stochastic derivative which can be used even for discrete variables. Instead of traditional calculus-based gradient, the algorithm utilizes musician$1 (Bs experience as a derivative in searching for an optimal solution. This can be a new paradigm and main reason in the successes of various applications. The goal of this book is to introduce major advances of the harmony search algorithm in recent years. The book contains 14 chapters with the following subjects: State-of-the-art in the harmony search algorithm structure; robotics (robot terrain and manipulator trajectory); visual tracking; web text data mining; power flow planning; fuzzy control system; hybridization (with Taguchi method or SQP method); groundwater management; irrigation ; logistics; timetabling; and bioinformatics (RNA structure prediction). This book collects the above-mentioned theory and applications, which are dispersed in various technical publications, so that readers can have a good grasp of current status of the harmony search algorithm and foster new breakthroughs in their fields using the algorithm.s
State-of-the-Art in the Structure of Harmony Search Algorithm -- Harmony Search Optimization Algorithm: Application to a Reconfigurable Mobile Robot Prototype -- Optimal Trajectory of Robot Manipulator Using Harmony Search Algorithms -- Visual Tracking Using Harmony Search -- Web Text Mining Using Harmony Search -- Population Variance Harmony Search Algorithm to Solve Optimal Power Flow with Non-Smooth Cost Function -- A Harmony Search Approach Using Exponential Probability Distribution Applied to Fuzzy Logic Control Optimization -- Hybrid Taguchi-Harmony Search Approach for Shape Optimization -- An Introduction to the Hybrid HS-SQP Method and Its Applications -- Solution of Groundwater Management Problems Using Harmony Search Algorithm -- Application of the Harmony Search Optimization in Irrigation -- The Application of Harmony Search in Fourth-Party Logistics Routing Problems -- A Harmony Search with Multi-pitch Adjusting Rate for the University Course Timetabling -- An Optimization Algorithm Based on Harmony Search for RNA Secondary Structure Prediction.
Keywords: Engineering; Artificial intelligence; Acoustics; Music; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Music; Acoustics